Maria Pia fecit / By Maria Pia: the observed and the observer. Some reflections on gender issues considering the case of Queen Maria Pia, the photographer - Flores, Teresa Mendes (2017)
his article discusses some aspects of the status of women amateur photographers during the turn of the 19th to 20th centuries, considering the case of the Portuguese Queen Maria Pia of Savoy (1847-1911). We acknowledge the difficulties of making the historiography of women photographers in Portugal, due to the scarcity of sources and archives, and the lack of questions about these absences and their reasons. These facts have contributed to a history of photography in Portugal that consists of a succession of male names of “great photographers”. Asking questions about “the other half”, as well as broadening conceptions of photography to include the diversity of their practices may contribute to highlight the gender constructions raised by photographic practice. It also will help to understand the factors contributing to the limited  access of Portuguese women to this practice and the lack of their public visibility, during this period.